The household knights of King John - Church, S. D. (Cambridge ; New York : Cambridge University Press, 1999)
This is the first full-length study of the elite group which surrounded King John, the household knights. As well as fighting for the king, they organised his armies, were involved in government, undertook diplomatic missions, controlled important castles, and proved themselves generally indispensable for the workings of English medieval government.
Preliminaries; Contents; Acknowledgements; List of abbreviations; 1 Introduction; 2 Recruitment into the royal military household; 3 Monarchy in action: the functions of the king's household knights; 4 The rewards of royal service; 5 Loyalty, civil war, and the household knights; 6 John's household knights during the minority of Henry III; 7 Some case histories; Conclusion; Bibliography; Index; Cambridge Studies in Medieval Life and Thought, Fourth series.
Includes bibliographical references (pages 156-167) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Great Britain -- History -- John, 1199-1216.; Knights and knighthood -- Great Britain -- History -- To 1500.; Royal households -- Great Britain -- History -- To 1500.; Great Britain -- History, Military -- 1066-1485.; Grande-Bretagne -- Histoire -- 1199-1216 (Jean); Grande-Bretagne -- Histoire militaire -- 1066-1485.; HISTORY; Knights and knighthood; Royal households; Great Britain; Hofhouding; Ridders; Engeland; To 1500; History; Military history